4(3y-3)=6y-24

Simple and best practice solution for 4(3y-3)=6y-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3y-3)=6y-24 equation:


Simplifying
4(3y + -3) = 6y + -24

Reorder the terms:
4(-3 + 3y) = 6y + -24
(-3 * 4 + 3y * 4) = 6y + -24
(-12 + 12y) = 6y + -24

Reorder the terms:
-12 + 12y = -24 + 6y

Solving
-12 + 12y = -24 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-12 + 12y + -6y = -24 + 6y + -6y

Combine like terms: 12y + -6y = 6y
-12 + 6y = -24 + 6y + -6y

Combine like terms: 6y + -6y = 0
-12 + 6y = -24 + 0
-12 + 6y = -24

Add '12' to each side of the equation.
-12 + 12 + 6y = -24 + 12

Combine like terms: -12 + 12 = 0
0 + 6y = -24 + 12
6y = -24 + 12

Combine like terms: -24 + 12 = -12
6y = -12

Divide each side by '6'.
y = -2

Simplifying
y = -2

See similar equations:

| -3(n-2)=3n-5+9 | | 2x-5(0)=16 | | 2ln(-x)+8=16 | | 2(8+2.5y)=16 | | -42=-36t | | 0-3(0)=6 | | 6t+2=2(3t+1) | | y=7-x/2 | | 3z^2+5z+1=3 | | 2x+x+4x=1715 | | 4x-3-6x+2=0 | | 0.25t+0.833=1.5t+0.67 | | (7-2j)-(7+2j)= | | 6x+8=4x+4-2x | | (y*2)+y=957 | | x+(x-3)=31 | | (x-3)(x-3)=20 | | 79-2x=10x-19 | | -5=z/3 | | 2g-32=-32 | | x-(x-1)=81 | | -6x+11=4x | | -2x/x-1+x+3/x^2-1 | | (y+9)+y=37 | | 6x-2=15-110 | | -16+x=43 | | 2x-5y=14 | | x-(x-1)=41 | | (2x+8)(x+4)=0 | | 27=9+x | | 2m^2-15m-27=0 | | -3m(n-2)=3n-5n+9 |

Equations solver categories